Ubertino da Casale, Chiara da Montefalco e lo Spirito di libertà. - LUCA POTESTÀ, GIAN (Scripta)
There is an obscure point in Ubertino da Casale's biography: his action against some friars of the Spoletana Valley, denounced by Chiara da Montefalco, tried by him and condemned as heretics (Arezzo, 1307). Sources on the secta Spiritus libertatis, particularly the depositions collected for Clare's canonization at the diocesan level (1308) and then as part of the apostolic trial (1318-1319), reveal that, before being denounced, the inquisites assiduously frequented the monastery as chaplains and confessors of the nuns, unscrupulously addressing with them issues concerning the dark side of mysticism as a liminal space. Re-reading the entire documentation of the first thirty years of the 14th century, the author deduces that Ubertino's polemic and then decisive action against the Spiritus libertatis aimed at marking a clear boundary against an experience perceived as dangerously close to that of the Spirituals. In this perspective, one understands both the distancing of Iacopone and Angela da Foligno from mystical doctrines they had previously held, and the awkward explanation with which Angelo Clareno tries to justify Ubertino's former frequentation of the heretic Bentivenga da Gubbio.